Investment Commitments to Telecommunications Reached a New Peak in 2007 - Izaguirre, Ada Karina; Perard, Edouard (World Bank, Washington, DC, 2012)
This note states that investment commitments to telecommunications projects with private participation in low- and middle-income countries amounted to US$75 billion in 2007, according to just-released data from the Private Participation in Infrastructure Project Database. That marked a new peak for the 1990-2007 periods. In 2007, 29 telecommunications projects with private participation reached financial or contractual closure in 28 low- and middle-income countries. Of these projects, 23 were greenfield merchant projects, involving investment of US$3.1 billion, and 6 were divestitures, with US$1.4 billion. Previously implemented greenfield projects accounted for another US$46.9 billion, and previously divested companies for US$23.6 billion. Four telecommunications projects were canceled or became distressed in 2007, bringing the total number to 42. These 42 contracts represent 5 percent of all telecommunications projects and 4 percent of investment commitments during 1990-2007. The report concludes, no telecommunications projects were concluded in 2007.